Common mechanisms underlying axonal transport deficits in neurodegenerative diseases: a mini review - Yang, Xiaoman; Ma, Zhuoran; Lian, Piaopiao; Xu, Yan; Cao, Xuebing (Frontiers in Molecular Neuroscience, 2023)
Many neurodegenerative diseases including Alzheimer's disease, Parkinson's disease, and amyotrophic lateral sclerosis are characterized by the accumulation of pathogenic proteins and abnormal localization of organelles. These pathological features may be related to axonal transport deficits in neurons, which lead to failures in pathological protein targeting to specific sites for degradation and organelle transportation to designated areas needed for normal physiological functioning. Axonal transport deficits are most likely early pathological events in such diseases and gradually lead to the loss of axonal integrity and other degenerative changes. In this review, we investigated reports of mechanisms underlying the development of axonal transport deficits in a variety of common neurodegenerative diseases, such as Alzheimer's disease, amyotrophic lateral sclerosis, Parkinson's disease and Huntington’s disease to provide new ideas for therapeutic targets that may be used early in the disease process. The mechanisms can be summarized as follows: 1) motor protein changes including expression levels and post-translational modification alteration; 2) changes in microtubules including reducing stability and disrupting tracks; 3) changes in cargoes including diminished binding to motor proteins. Future studies should determine which axonal transport defects are disease-specific and whether they are suitable therapeutic targets in neurodegenerative diseases.